A comprehensive study on influence of operating parameters on agglomeration of ashes during biomass gasification in a laboratory-scale gasification system. (15th September 2020) - Yao, Xiwen; Hu, Yonglu; Ge, Ji; Ma, Xingzong; Mao, Jianyu; Sun, Lu; Xu, Keqiang; Xu, Kaili
Highlights: Ash agglomeration behaviour during corncob gasification was studied and elucidated. Effects of operating parameters on ash deposits during gasification were studied. A higher equivalent ratio favored the capture of more volatile species in cyclone. A lower temperature favored the retention of Si, Al and Fe in the gasifier ashes. With increasing residence time, the slagging degree of fly ashes could be enhanced. Abstract: Ash residues produced from biomass gasification could agglomerate and cause severe ash-related problems. The objectives of this study were to determine the impacts of different operating parameters (including equivalent ratio (ER), residence time (RT), and gasification temperature (GT)) on ash deposits during corncob gasification and to further elucidate ash agglomeration mechanisms. The results indicated that the major difference between the ashes in gasifier and the cyclone fly ash (CFA) in mineralogy was that the CFA had a higher content of potassium-bearing compounds, particularly sylvite and potassium silicates, the contents of which could be as high as 47.33 wt% and 12.61 wt%, respectively. Compared with the gasifier fine ash (GFA), the microstructure of gasifier slagging block (GSB) seemed to be much denser and could be divided into three types, skeleton structure, porous texture, and dense structure. However, the melting of CFA was more severe than that of the gasifier ashes. During gasification, a higher ER and a higher GT favored the capture of more volatile species such as K, Ca, S and Cl in the cyclone while a lower GT and an increased RT favored the retention of Si, Al and Fe in the bottom residues. Moreover, when the ER was increased, less silicate minerals could be concentrated on the CFA. With regards to the operations performed at different times, no obvious variation in the ash mineralogy was observed. The ER had little influence on fly ash morphology while the slagging degree of fly ash could be enhanced with the increasing of RT.